2006
DOI: 10.1021/jp057063u
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Reactions of Benzoxazole. Single Pulse Shock Tube Experiments and Quantum Chemical Calculations

Abstract: The thermal decomposition of benzoxazole diluted in argon was studied behind reflected shock waves in a 2 in. i.d. single-pulse shock tube over the temperature range 1000-1350 K and at overall densities of approximately 3 x 10(-5) mol/cm(3). Two major products, o-hydroxybenzonitrile at high concentration and cyclopentadiene carbonitrile (accompanied by carbon monoxide) at much lower concentration, and four minor fragmentation products resulting from the decomposition were found in the postshock samples. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…In the present case the bond length of C 22 -C 24 and C 21 -C 23 are 1.4988 and 1.4923 Å, the bond length is very high due to the presence of methyl group. The bond length of C 21 -C 22 is 1.383 Å which is agreement with the reported value [67]. Bigotto et al [68] reported the bond length of C 21 -C 22 as 1.3827 Å.…”
Section: Optimized Geometrysupporting
confidence: 89%
See 1 more Smart Citation
“…In the present case the bond length of C 22 -C 24 and C 21 -C 23 are 1.4988 and 1.4923 Å, the bond length is very high due to the presence of methyl group. The bond length of C 21 -C 22 is 1.383 Å which is agreement with the reported value [67]. Bigotto et al [68] reported the bond length of C 21 -C 22 as 1.3827 Å.…”
Section: Optimized Geometrysupporting
confidence: 89%
“…Lifshitz et al [67] reported the bond lengths for C 22 -C 24 , C 21 -C 23 as 1.374 and 1.4 Å. In the present case the bond length of C 22 -C 24 and C 21 -C 23 are 1.4988 and 1.4923 Å, the bond length is very high due to the presence of methyl group.…”
Section: Optimized Geometrysupporting
confidence: 45%
“…However, the studies performed at −40 °C (in methylcyclohexane) seemed to indicate the formation of a different photoproduct, 2-isocyanophenol 4 , which promptly decayed back to 1 upon heating to room temperature . The thermal reaction of benzoxazole under single-pulse shock-tube conditions was also studied . Under those conditions, the main isomerization product was 2-cyanophenol 3 , which subsequently decomposed to cyano-cyclopentadiene and CO.…”
Section: Introductionsupporting
confidence: 67%
“…18 The thermal reaction of benzoxazole under single-pulse shock-tube conditions was also studied. 19 Under those conditions, the main isomerization product was 2-cyanophenol 3, which subsequently decomposed to cyano-cyclopentadiene and CO.…”
mentioning
confidence: 99%
“…Moreover, the ring expansion and isomerization products are found to be of very high yield. Experimental results were obtained, modeling and quantum chemical calculations of potential energy surfaces have been performed on molecules such as methylpyrrole, [1][2][3] dimethylpyrrole, 4 methylindole, 5 methylcyclopentadiene, [6][7][8] methylindene (quantum chemical calculations) 9 and others. Some of the studies have been published and some are still in the process of data reduction.…”
Section: Introductionmentioning
confidence: 99%